(untitled) (Al-Academy, 2017)
This research deals with process of artistic conception of nature’s images between becoming and buration, as an attempt to transfer the philosophical concepts to art via it’s structural applications in forming the picture, due to the importance of these concepts which might be engaged with the vision of the artist in his own and subjective contention with the nature. The research consists of four chapters, first one included the problem of the research, importance, need to the research and the aim of the research represented by process of artistic conception of nature’s images between becoming and buration. Also included the limits of research and most important terms. Second chapter included theoretical frame that consists of three sections. First section was about conception and its meaning and techniques. Second section was about : Essence of the relation between becoming and buration. While third section was about the artistic conception of nature’s images. The theoretical section ended with indications. Third chapter included procedures of the research represented by the community and sample of the research which is consisted of six artistic works and then analyzing them. The research ended with the fourth chapter which dealt with the results, conclusions, recommendation and suggestion. One of the results was : the researcher launched drawing the nature’s images from the becoming described as a plastic matter saturated with the dynamic movement against stability, silence, mechanical technique and working on modifying the quantity into artistic query featured with continuity .